Outside Front Cover: Volume 25 Issue 1. (16th February 2022) - Desborough, Jane; Parkinson, Anne; Lewis, Fiona; Ebbeck, Harry; Banfield, Michelle; Phillips, Christine
Abstract : Outside Front Cover Caption : The cover image is based on the Research Article A framework for involving coproduction partners in research about young people with type 1 diabetes by Jane Desborough et al., https://doi.org/10.1111/hex.13403 .